Thoracic Trauma: Aortic Injuries - Monga, Akhil; Patil, Santosh B.; Cherian, Mathew; Poyyamoli, Santhosh; Mehta, Pankaj (Seminars in Interventional Radiology, 2021)
Thoracic aortic injuries caused by high impact trauma are life-threatening and require emergent diagnosis and management. With improvement in the acute care services, an increasing number of such injuries are being managed such that patients survive to undergo definitive therapies. A high index of clinical suspicion is required to order appropriate imaging. Computed tomography angiography is used to classify the injuries and guide treatment strategy. While low-grade injuries might be managed conservatively, high-grade injuries require urgent surgical or endovascular intervention. Over the past decade, endovascular repair of the thoracic aorta with or without a surgical bypass has become the preferred treatment with reduced mortality and morbidity. Rapid advancements in the stent graft technology have reduced the anatomic barriers to endovascular therapy and increased the confidence of the operators. Detailed planning prior to the procedure, understanding of the anatomy, correct choice of hardware, and adherence to technical protocol are essential for a successful endovascular procedure. These patients are often young and the limited data on the long-term outcome of aortic stent grafts make a case for a robust follow-up protocol.
Keywords: traumatic aortic injury; aortic trauma; TEVAR; endovascular repair; interventional radiology